Taquari, a fodder bamboo from the cerrados of central Brazil - Filgueiras, Tarciso S.; Pereira, Benedito Alísio S. (Pesquisa Agropecuaria Brasileira, 2014)
The fire-adapted bamboo Actinocladum verticillatum (Taquari) from the Brazilian Cerrado is presented as a potential fodder grass, especially for the dry periods of Central Brazil. A chemical analysis of the leaves (11.8% protein) is presented together with some ecological observation. Research needs are discussed.